Conservation agriculture in cereal systems of South Asia: effect on crop productivity and carbon-based sustainability index - Jat, Mangi Lal; Jat, Kumar Raj; Gupta R; Gopal R (2011)
Maize, wheat and rice, the major cereals grown as monoculture or in sequence, contribute the bulk of food and incomes in rural regions of South Asia. The large increases in food production are one of the greatest achievements of the second half of the 20th century, but sustaining these gains is a major challenge. Inappropriate management practices and intensive cropping in the past have led to the twin challenges of resource depletion and decelerating productivity growth of cereal crops. The efficiency and sustainability of a production system depends on system-based management optimization of crop yields, economic benefits, and environmental impacts. The long term sustainability of a cropping system depends on its carbon inputs, outputs and carbon use efficiency which indicate long-term sustainability in terms of yield, environment and ecology. Similarly, efficient utilization of carbon-based resources mitigates the increasing level of CO2 in the environment. Most of the indices used by researchers in the past to evaluate the sustainability of any cropping systems have been based on economic yield or yield sustainability, without giving due emphasis to environmental issues. In this study, three major cereal systems (rice-wheat, rice-maize and maize-wheat) were evaluated under conservation agriculture practices and compared with conventional tillage in terms of yield, carbon (C) inputs and outputs, and a carbon based sustainability index.